The influence of the window shopping learning model in increasing student geography learning activities at SMAN 12 Pekanbaru. - Zaharani, Kasisha; Afryansih, Nila; Setriani, Loli (Universitas Lampung, 2023)
This study aims to find out and analyze the effect of the Window Shopping learning model in school inscreasing student geography learning activities at SMAN 12 Pekanbaru. The low learning activity of student in learning, especially in geography subjects in class XI IPS at SMAN 12 Pekanbaru, Riau Province. This research was conducted in order to find out the results of the influence of the Window Shopping learning model which is expected tobe able to increase student learning activities in geography subjects. This research method is quantitative. The type of research is quasi experiment. The technique used in sampling is random sampling technique. The instrument used in this study was the observation sheet which was carried out during the geography lesson. The population is all students of class XI IPS at SMAN 12 Pekanbaru for the 2022/2023 academic year. The samples taken were class XI IPS 2 as an experimental class with 35 students. The results showed that the hypothesis was accepted, which means that the geography learning activities of the experimental group using the Window Shopping learning model were more able to increase students geography learning activities compared to the geography learning activities in the control group using conventional methods.